Influence of lactic acid bacteria strains on ester concentrations in red wines: Specific impact on branched hydroxylated compounds. (15th January 2018) - Gammacurta, Marine; Lytra, Georgia; Marchal, Axel; Marchand, Stéphanie; Christophe Barbe, Jean; Moine, Virginie; de Revel, Gilles
Highlights: Six single-varietal red wines were made on industrial and experimental scale. Experimentations were made using several yeast and LAB strains in two vintages. The levels of most compounds were slightly impacted by LAB strain. Branched hydroxylated esters were strongly influenced by the bacteria strain. Only the R form of branched hydroxylated esters has been observed after MLF. Abstract: This research investigated the influence of lactic acid bacteria (LAB) strains on ester levels in Bordeaux red wines. These wines were made in five Bordeaux areas in two vintages, using three yeast strains. Malolactic fermentation (MLF) was carried out using industrial starters or indigenous strains, each in triplicate. Ester concentrations were determined by liquid-liquid-extraction- or HS-SPME-GC/MS at various stages in the winemaking process. The levels of most compounds were slightly impacted by LAB, depending on grape variety. Nevertheless, branched hydroxylated esters, such as ethyl 2-hydroxy-3-methylbutanoate and ethyl 2-hydroxy-4-methylpentanoate were the only compounds to be strongly influenced by the bacteria strain, regardless of matrix composition or the yeasts used for alcoholic fermentation. Moreover, the effect observed after MLF persisted over time, for at least 12 months. These esters are apparently important markers of LAB esterase activity. To our knowledge, this was the first time they had been identified in this role.